Environmental impact assessment of development projects improved by merging species distribution and habitat connectivity modelling. (1st July 2019) - Tarabon, Simon; Bergès, Laurent; Dutoit, Thierry; Isselin-Nondedeu, Francis
Abstract: Environmental impact assessment (EIA) is performed to limit potential impacts of development projects on species and ecosystem functions. However, the methods related to EIA actually pay little attention to the landscape-scale effects of development projects on biodiversity. In this study we proposed a methodological framework to more properly address the landscape-scale impacts of a new stadium project in Lyon (France) on two representative mammal species exemplary for the endemic fauna, the red squirrel and the Eurasian badger. Our approach combined species distribution model using Maxent and landscape functional connectivity model using Graphab at two spatial scales to assess habitat connectivity before and after development project implementation. The development project had a negative impact on landscape connectivity: overall habitat connectivity ( PC index) decreased by −6.8% and −1.8% and the number of graph components increased by +60.0% and +17.6% for the red squirrel and the European badger respectively, because some links that formerly connected habitat patches were cut by the development project. Changes affecting landscape structure and composition emphasized the need to implement appropriate avoidance and reduction measures. Our methodology provides a useful tool both for EIA studies at each step of the way to support decision-making in landscape conservation planning. The method could be also developed in the design phase to compare the effectiveness of different avoidance or mitigation measures and resize them if necessary to maximize habitat connectivity. Highlights: The combination of modelling methods allows to better quantify habitat connectivity. Habitat connectivity was modelled before and after an urban development project. The diachronic analysis confirms the potential effect on landscape connectivity. Connectivity changes emphasized the need to implement conservation measures.